2022
DOI: 10.1177/21925682221136492
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes of Deep Extensor Neck Muscles in Relation to the Maximum Level of Cord Compression and Canal Compromise in Patients With Degenerative Cervical Myelopathy

Abstract: Study design Cross-sectional study Objectives To examine the relationship between morphological changes of the deep extensor neck muscles in patients with degenerative cervical myelopathy (DCM) and the level of maximum spinal cord compression (MSCC) and canal compromise (MCC). A secondary objective was to examine the relationship between muscle morphological changes with neck pain and functional scores related to neck pain and interference. Methods A total of 171 patients with DCM were included. Total cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Many studies have found that muscle denervation is one of the main factors contributing to muscle atrophy and fatty infiltration of paravertebral muscles in patients with CSM. 11,12,17,18 The deep paravertebral muscles, especially the MF, are mainly composed of type I muscle fibers with a high density of spindles. Therefore, changes in the DEM morphology and composition can lead to impairments in precise motor control, proprioception, and kinesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have found that muscle denervation is one of the main factors contributing to muscle atrophy and fatty infiltration of paravertebral muscles in patients with CSM. 11,12,17,18 The deep paravertebral muscles, especially the MF, are mainly composed of type I muscle fibers with a high density of spindles. Therefore, changes in the DEM morphology and composition can lead to impairments in precise motor control, proprioception, and kinesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the FCSA and FCSA/CSA of the MF and the CSA and FCSA of the SSCe declined with increasing age. Many studies have found that muscle denervation is one of the main factors contributing to muscle atrophy and fatty infiltration of paravertebral muscles in patients with CSM 11,12,17,18 . The deep paravertebral muscles, especially the MF, are mainly composed of type I muscle fibers with a high density of spindles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations